2022
DOI: 10.1002/jcla.24553
|View full text |Cite
|
Sign up to set email alerts
|

The association between Monocyte‐to‐Lymphocyte ratio and postoperative delirium in ICU patients in cardiac surgery

Abstract: Delirium, which is defined as an acute confessional condition whose characteristics include impaired mental state, is correlated with significant economic costs, high incidence of falls and fall-related accidents, self-removal of medical equipment, long-term hospitalizations, and even increased fatality rates. 1,2 The incidence of postoperative delirium (POD) in heart surgery patients ranges from 50 to 70 percent. According to many prospective studies [3][4][5] , POD is correlated with significant short-term r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…6 A). This is consistent with previous research findings that inadequate postoperative pain management [ 61 ], prolonged anesthesia duration [ 63 ], electrolyte imbalance, metabolic abnormalities [ 64 ], abnormal liver and kidney function [ 3 ], carbon dioxide retention [ 65 ], monocyte-to-lymphocyte ratio (MLR) [ 66 ], and decreased serum albumin [ 67 ] can all contribute to the occurrence of postoperative delirium. By comparing the summary plots of the two feature sets and considering the previous outcome indicators, it can be observed that despite having only 19 features, the selected feature set still has meaningful predictive power for the outcome.…”
Section: Discussionsupporting
confidence: 91%
“…6 A). This is consistent with previous research findings that inadequate postoperative pain management [ 61 ], prolonged anesthesia duration [ 63 ], electrolyte imbalance, metabolic abnormalities [ 64 ], abnormal liver and kidney function [ 3 ], carbon dioxide retention [ 65 ], monocyte-to-lymphocyte ratio (MLR) [ 66 ], and decreased serum albumin [ 67 ] can all contribute to the occurrence of postoperative delirium. By comparing the summary plots of the two feature sets and considering the previous outcome indicators, it can be observed that despite having only 19 features, the selected feature set still has meaningful predictive power for the outcome.…”
Section: Discussionsupporting
confidence: 91%
“…As studies mentioned, a high level of NLR has been identified as an independent risk factor for POD in acute ischemic stroke and orthopedic surgery (Guldolf et al., 2021 ; Li et al., 2022 ). Also, other inflammatory markers ratios, such as MLR and PLR, played a prominent role in predicting POD after cardiac surgery (Şaşkin et al., 2022 ; Su et al., 2022 ). Interestingly, a recent study showed the connection between higher PWR and poor clinical consequences in patients with acute ischemic stroke (Amalia & Dalimonthe, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), as well as platelet‐to‐white blood cell ratio (PWR) have been acknowledged as potential predictors of POD in head and neck free‐flap reconstruction or abdominal surgery (Ida et al., 2020 ; Kinoshita et al., 2021 ). Also, a recent study showed that the monocyte‐to‐lymphocyte ratio (MLR) was independently correlated with POD in intensive care unit (ICU) patients after cardiac surgery (Su et al., 2022 ). Furthermore, the above inflammatory indexes were capable of predicting postoperative complications and long‐term prognosis in thoracic oncology surgery (Ginesu et al., 2022 ; Tsukioka et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Delirium during hospitalization was assessed using the Confusion Assessment Method by the ICU. We utilized this approach, searching all the ICD codes associated with included subjects for the following terms: (1) delirium, (2) encephalopathy, (3) altered mental status, (4) confusion, (5) mental disorder, (6) hallucination, (7) delusion, and (8) cognitive impairment/deficit [ 41 , 42 , 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%